Entre imagens e palavras: educação e nacionalismo no Estado Novo (1937-1945) - Veronica Albano Viana Costa (2009)
In the period between 1937 and 1945, New State used various cultural elements as socialization strategy from the nationalistic politics culture. Although the diffusion and legitimation effort of this idea has been revealed in different social life dimensions, the role attributed to the education was relevant, particularly the schooling one, as privileged instrument to conform, morally and civically, the new generations. Starting from this premise, that research remained in the confluence between Education History and Politics History instigated from the relations between education and Nationalism. The research focused on the production and appropriation forms of nationalist discourse constructed through images and words and propagated in official school books. The approach of the works was realized in triangulated form with Cultura Política magazine and with materials of civic-pedagogical nature, such as posters, cards, notebooks and official and unofficial literary works in order to deconstruct the estadonovista discourse, searching its symbolic references, as well as its appropriations and approaches with representations propagated in cultural goods of civic- pedagogical nature to the light of the imaginary and representations concepts. It was appealed to oral History for the apprehension of some appropriation indications of the nationalistic discourse, as well as the representations about the nationality values appropriated by the young students from that period who had circulated in the infantile section Malazarte in the newspaper Estado de Minas.